A HISTORY CASE OF ADALIMUMAB TREATMENT IN A FEMALE PATIENT WITH JUVENILE ARTHRITIS AND UVEITIS AS MANIFESTATIONS OF CROHN’S DISEASE - V. A. Malievskii; A. A. Nijevitch; E. P. Pervushina; L. Yu. Sapronova (Вопросы современной педиатрии, 2013)
A history case of severe juvenile arthritis with uveitis as manifestations of Crohn’s disease, resistant to standard immunosuppressive therapy and treatment with chimeric anti-tumor necrosis factor-alpha monoclonal antibody is represented in this article. Adalimumab — recombinant monoclonal antibody, which peptides sequence is identical to human IgG1, allowed to arrest active stage of inflammatory process, uveitis and intestinal manifestations of Crohn’s disease, as well as to restore function of involved joints almost completely. This history case confirms high efficacy of adalimumab in patients with Crohn’s disease manifested with juvenile arthritis complicated with uveitis, and allow to recommend this medicine as first-line genetically-engineered biological agent in treatment of such patients.